Genodermatoses Picture: Difficulties Faced And Way Forward in Nepal - Parajuli, Niraj; Baskota, Rabindra; Jain, Ritu (Journal of Nepal Health Research Council, 2023)
Genodermatoses are group of genetic disorders that present with cutaneous manifestations. The exact prevalence on many of these conditions are unknown due to its rarity, need of specialized tests for diagnosis and lack of proper reporting system. Most of the patients are faced with life-long disability and associated stigma. There is a need for specialized centers for proper diagnosis of these conditions and a very elaborated yet simple reporting system in Nepal. These rare conditions should be kept in priority by the government in align with the sustainable development goals to ensure healthy-lives and promote well-being for all. A wider engagement of patient-led support groups might be useful in providing necessary information on the disease to the general population and alleviate the stigma associated with these diseases. Keywords: Epidermolysis bullosa; genodermatoses; rare diseases; Nepal